ACTANTIAL MODEL IN THE NELYUBOV MOVIE - Haryadi, Jasmine Disca; Kaprisma, Hendra (Capture : Jurnal Seni Media Rekam, 2021)
Through the characters of Zhenya and Boris, the film Nelyubov (2017) explores the issue of a toxic marriage. The story's theme reflects the complexities of the characters' relationships and the resulting problems. This theme adds intrigue to the film's problem articulation, particularly how the film's conflict can be constructed. Accordingly, this study seeks to identify the actant schemes created in the Nelyubov film. This study examines the location of individuals in the film using Algirdas Julien Greimas' Actantial Model theory. Further, this article employs Mills' Discourse Analysis and Smith's Interpretative Phenomenological Analysis (IPA). The results indicate representations for the subject, object, helper, opposer, sender, and receiver in the Nelyubov film, allowing for the fulfillment of the three kinds of axis: the axis of desire, the axis of power, and the axis of transmission/knowledge. The film's subject is Zhenya, and the object is the happiness he seeks.